2002
DOI: 10.1080/10298420290007646
|View full text |Cite
|
Sign up to set email alerts
|

Differential pattern of expression of voltage-gated sodium channel genes following ischemic brain injury in rats

Abstract: This study investigated the effects of brain ischemia on sodium channel gene (NaCh) expression in rats. Using quantitative RT-PCR, our findings demonstrated the expression ratio of NaCh genes in normal rat brain to be Na(v)1.1 > Na(v)1.8 > Na(v)1.3 > Na(v)1.7 (rBI > PN3 > rBIII > PN1). In contrast, brain injury caused by middle cerebral artery occlusion (MCAo) for 2 h followed by reperfusion significantly down-regulated Na(v)1.3 and Na(v)1.7 genes in both injured and contralateral hemispheres; whereas the Na(v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
26
4

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 43 publications
6
26
4
Order By: Relevance
“…1, while other NaCh genes were not significantly affected by direct activation of these voltage-gated sodium channels. These data are consistent with our recent in vivo findings in which temporary middle cerebral artery occlusion (MCAo) produced a time-dependent down-regulation of Nav1.1 gene in the injured hemisphere (Yao et al, 2002). Furthermore, the present study is 1) the first to demonstrate a selective reversal of veratridine-mediated down-regulation of Navl.1 gene expression and 2) documents a direct correlation of RS-100642 neuroprotection and reversal of sodium channel gene expression.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…1, while other NaCh genes were not significantly affected by direct activation of these voltage-gated sodium channels. These data are consistent with our recent in vivo findings in which temporary middle cerebral artery occlusion (MCAo) produced a time-dependent down-regulation of Nav1.1 gene in the injured hemisphere (Yao et al, 2002). Furthermore, the present study is 1) the first to demonstrate a selective reversal of veratridine-mediated down-regulation of Navl.1 gene expression and 2) documents a direct correlation of RS-100642 neuroprotection and reversal of sodium channel gene expression.…”
Section: Discussionsupporting
confidence: 81%
“…Although these results differ slightly from those reported earlier from our laboratory in adult rat brain (Yao et al, 2002) where the abundance of Navl.2 channel mRNA is also greatest, but followed by Navl.1, Nal.8, Nal.3 and Na'1.7 mRNA. It should be noted that in both cases Navl.2 gene expression is the most abundant, whereas the Na1l.7 transcript is the least abundant.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…This phenomenon may represent an endogenous response to limit energy utilization due to the excitotoxic state of the ischemic brain but may also participate in the electrophysiological disturbances inherent to ischemic brain injury. Previous studies have demonstrated the down-regulation the NaCh subunits Na v 1.1, Na v 1.2, Na v 1.3, Na v 1.7, Na v 1.8 following focal ischemic brain injury in the rat (Yao et al, 2002). In particular, mRNA levels of Na v 1.1 exhibited the most dramatic and sustained drop with greater than 75% reductions at 48 h post-MCAo as compared to normal levels (Yao et al, 2002).…”
Section: Introductionmentioning
confidence: 92%